Flow of Liquid in Flat Gaps of the Satellite Motor Working Mechanism - Sliwiński Paweł (Polish Maritime Research)
The article describes the methodology and results of investigations of the flow of oil and HFA-E emulsion in flat gaps of the working mechanism of a satellite motor. The flow of liquid in those gaps is turbulent and not fully developed. The article presents two methods of modelling this flow. Method I makes use of the Darcy-Weisbach formula, while Method II bases on the assumption that in the variable-length gaps the flow is turbulent in the area where the length is the smallest and laminar where the length is the largest. Consequently, the flow in such gaps can be modelled as the sum of laminar and turbulent flows. The results obtained in the experiment have made the basis for calculating relevant coefficients and assessing the proportion of turbulence in the flow modelled using both methods